Kardiochirurgia wad wrodzonych Transcatheter closure of atrial septal defects – own experience after 502 procedures - Szkutnik, Małgorzata; Białkowski, Jacek; Banaszak, Paweł; Kusa, Jacek; Baranowski, Jacek; Karwot, Blandyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Introduction: Percutaneous closure has became treatment of choice in selected cases of atrial septal defects type II (ASD). Aim: To show own experience in this field. Material and methods: Between 1997-2005 there were 502 patients (pts) treated. Their age ranged from 0,4 to 74 (mean 24) years. Amplatzer occluders were applied in 468 pts, Starflex double umbrella in 32 pts and Helex in 2. The defects were devided for simple and complex form of ASD. The latter included multiple ASDs (86 pts), large defects with deficient aortic rim (56 pts), with coexisted other heart defect (13 pts) and cases performed in small children (31 pts). Results: The procedures were finished successfully in 97% of pts. Complications included embolization in 3 cases, temporay rhythm disturbances in 3 pts and transient left ventricular failure in another 3 pts. During first months after implantation 10% of pts complained on headache. Conclusion: Transcatheter closure has gained important place in the treatment of pts with ASD.